Exploring the links between the use of NbS, mindshifts and transformative urban coalitions to promote climate resilience within an ongoing reurbanization process. The case of Villa 20, Buenos Aires - Hardoy, Jorgelina; Motta, Jorge Martín; Kozak, Daniel; Almansi, Florencia; Reverter, Tomás; Costello, Marcela (Frontiers in Sustainable Cities, 2022)
In recent decades, informal settlement upgrading and housing deficit in Latin America has been addressed through a variety of urban programs, usually structured around physical-spatial and social actions with an emphasis on the provision of basic infrastructure and services, improved accessibility and connectivity and new housing, mostly done by conventional means. In general, they fail to incorporate new frameworks that provide solutions with strong environmental roots, such as Nature-based Solutions (NbS), Blue-Green Infrastructure (BGI) or Ecosystem-based Adaptation (EbA). This article explores the links between the use of NbS, and equity and justice in a particular setting: Villa 20, an informal settlement in the City of Buenos Aires that is undergoing a participatory urban upgrading process with a strong participatory platform made up of multiple spaces and devices for consensual decision-making on re-urbanization aspects. In Villa 20, several interrelated projects and programs are focusing on sustainability. In particular, the Transformative Urban Coalitions (TUC) of the International Climate Initiative (IKI) is connecting decarbonization with urban inequalities and urban justice. The article reflects on some of the initial outcomes of the TUC program that builds upon the ongoing participatory upgrading process. Three instances of transformative change are reviewed: 1. Within government teams; 2. Within the community leaders; and 3. Within the Urban Lab. In addition to exploring the links between the use of NbS, equity and climate justice in marginalized urban social contexts; the article also looks into the social setting and methods and tools that promote mindset shifts that in turn allow for changes in real world settings that can inspire further transformation; and assesses the building up of a transformative urban coalition. With this, we aim to better understand the possibilities and potential implications of implementing NbS in marginalized social contexts in cities of the global south, contributing both to closing the knowledge gap and re-thinking future policies and programs.